Inflectional affixes in j.k. Rowling's novel Harry Potter and the Chamber of Secrets - Rachael Joy Nabasa Silalahi; Ronaldo Ersan; Cindy Ardauli; Esron Ambarita (Indonesian Journal Education, 2026)
This study examines the use of inflectional affixes in J.K. Rowling’s novel Harry Potter and the Chamber of Secrets from a morphological perspective. The research aims to identify the types of inflectional affixes and explain their grammatical functions in the narrative context. A descriptive qualitative method was employed, with data collected from selected words and sentences in the novel. The analysis is based on Yule’s (2010) theory, which classifies English inflection into eight categories: plural, possessive, third person singular present, past tense, past participle, progressive, comparative, and superlative. The findings reveal a total of 34 inflectional forms, consisting of five plural forms, five possessives, three third person singular forms, ten past tense forms, three past participles, five progressive forms, two comparative forms, and two superlative forms. These results demonstrate that inflectional affixes play an essential role in conveying grammatical meaning without altering word class or core meaning. This study contributes to morphological analysis by illustrating the practical use of English inflectional affixes in literary texts and may serve as a reference for students and researchers in linguistics and English language studies.